The Stress Level of Final Year Students Affects the Menstrual Cycle during The Covid-19 Pandemic - Arliandari, Anggita; Rohmayanti, R; Wijayanti, Kartika (Prosiding University Research Colloquium, 2022)
Stress is now an unavoidable part of human life. One of the people who are vulnerable to stress is final year students, especially women. Women who do not have a strong defense against stress, the body will react to changes in the menstrual cycle. This study aims to determine the relationship between stress and menstrual cycles in FIKES UNIMMA students during the Covid-19 pandemic. The sample in this study were final year students of FIKES UNIMMA who met the inclusion criteria of 105 respondents, the sample was taken using proportional random sampling technique. The data was processed using the Spearman statistical test and the results obtained (p = 0.002 and r = 0.296). There is a relationship between stress and the menstrual cycle of final year students of FIKES UNIMMA during the Covid-19 pandemic with a positive correlation direction and sufficient strength of the relationship. Stress levels at a moderate level in final year students can affect the menstrual cycle during the Covid-19 pandemic.